2019
DOI: 10.1155/2019/3452180
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Degradation of Single Junction Amorphous Silicon Modules (a-Si:H)

Abstract: This study examines the degradation of single junction amorphous silicon (a-Si:H) photovoltaic (PV) modules. It summarises the main results obtained from over 7 years of field investigation of the degradation mechanisms of a-Si:H modules. The investigation was based on performance parameters such as fill factors, parasitic resistances, and ideality factors. The initial efficiencies for these modules were in accordance with the expected values; however, a significant decrease was observed during the monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In addition, adhesion degradation between various layers affects interface binding energy and aids the delamination of the layers of solar cells. This can lead to low output and ultimately result in premature failure as reported in previous study by Osayemwenre's @ et al, 2019. In that study in 7 years since the beginning of the monitoring process, two modules were observed to have failed [20][21][22]. Additional measurements were taken for the defective and non-defective samples at the intrinsic region, starting from the p/i interface to i/n interface.…”
Section: Adhesionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, adhesion degradation between various layers affects interface binding energy and aids the delamination of the layers of solar cells. This can lead to low output and ultimately result in premature failure as reported in previous study by Osayemwenre's @ et al, 2019. In that study in 7 years since the beginning of the monitoring process, two modules were observed to have failed [20][21][22]. Additional measurements were taken for the defective and non-defective samples at the intrinsic region, starting from the p/i interface to i/n interface.…”
Section: Adhesionmentioning
confidence: 86%
“…All the images of AFM tips used were with a high-resolution scanning electron microscope (SEM) before and after the measurement, to check for any tip modification that could alter the pull-off force of the cantilever tip. This technique is automatically able to calculate the pull-off force from the force-distance plot using the calibration procedure before the measurement [19,20]. To determine the appropriate position of the region of interest, an extremely low value was used for the elastic constant and equilibrium spacing.…”
Section: Identification Of Interfacial Locations Using Force Quantitamentioning
confidence: 99%
“…The degradation of a-Si:H was studied by Osayemwenre and Meye, and they observed that efficiency decreased considerably during the monitored time period. Efficiency was reduced by 0.2% with each degree of increase in temperature [31].…”
Section: Amorphous Silicon Thin Filmsmentioning
confidence: 97%
“…Studies have revealed that these chemicals include hydrochloric acid, nitric acid, hydrogen fluoride, 1,1,1-trichloroethane, acetone and sulphuric acid. Thin-film PV modules contain more toxic materials than conventional silicon PV modules [10], [12]. As PV modules begin to degrade and with continued exposure to harsh environmental conditions, moisture and water ingress occurs.…”
Section: A Background Of Studymentioning
confidence: 99%
“…As PV modules begin to degrade and with continued exposure to harsh environmental conditions, moisture and water ingress occurs. When delamination of the PV module's protective layers occurs, it contaminates any rainwater harvested from it [12]. If such water is consumed or used for domestic purposes it can affect human health negatively.…”
Section: A Background Of Studymentioning
confidence: 99%